Integration of Six Sigma and ISM to improve Supply Chain Coordination – A conceptual framework - Pratima Mishra; Rajiv Kumar Sharma (International Journal of Production Management and Engineering)
To achieve competitiveness and to improve supply chain performance, supply chain coordination (SCC) is considered as a key challenge by the companies to satisfy their customers. In today’s turbulent economic environment, SCC is a topic of great significance among business houses because SCC creates understanding, molds human behavior and improve competitiveness.  As observed from literature that the dynamics of global market has resulted in serious pressure and distraction to activities of various supply chain entities i.e. suppliers, manufacturer, distributors, wholesaler, retailers and customers, which ultimately affects the SC performance. Thus, supply chains are exposed to risks due to uncertain and turbulent economic environment. To overcome these challenges, authors in this study developed a conceptual framework for knowledge management based on Six Sigma and ISM which can be used to study various supply chain dimensions be it human, process or quality dimensions. The main advantage of this framework is that it not only helps to understand information regarding the strength and weaknesses of various supply chain entities in a supply chain but also helps to determine the structural relationship among key dimensions of interest. The proposed framework can be applied by industries to model and analyze their processes effectively, compare their performance both within and outside their industry segment and thus improve competitiveness by following knowledge management practices.